Engaging students in public discourse using ICT - Chan, Mei Yuit (Assumption University of Thailand, 2011)
An important objective of university education is to produce graduates who will be leaders of a community, the nation, and the world. In today’s era of the internet and globalisation, where discursive and rhetorical skills feature strongly in influencing public opinion and mobilising social action, a leader needs to possess the ability to participate effectively in pubic discourse, that is, communication in the public sphere that touches on the concerns of the community and the world. This is true for leaders across all disciplines and professions, business leaders included. This paper presents insights obtained from an initiative carried out at Universiti Putra Malaysia whereby the online discussion board or forum platform was used as a means to inculcate the skills of public discourse in English through the online media. Practical aspects for the implementation of an online forum project that include considerations for level of participation, use of English, moderation, public orientation, and affective barriers are also discussed.